H-1Bs: How do they stack up to US born workers? - Magnus Lofstrom; Joseph Hayes (Institute for the Study of Labor (IZA), 2011)
Combining unique individual level H-1B data from U.S. Citizenship and Immigration Services (USCIS) and data from the 2009 American Community Survey, we analyze earnings differences between H-1B visa holders and US born workers in STEM occupations. The data indicate that H-1Bs are younger and more skilled, as measured by education, than US born workers in the same occupations. We fail to find support for the notion that H-1Bs are paid less that observationally similar US born workers; in fact, they appear to have higher earnings in some key STEM occupations, including information technology.
urn:nbn:de:101:1-201203016393
Keywords: J8; J15; J18; J31; J61; 330; temporary workers; H-1B; immigration; high-skill; STEM; Leiharbeit; Internationale Arbeitsmobilität; Qualifikation; Lohnstruktur; Bevölkerung; USA